2019
DOI: 10.47102/annals-acadmedsg.v48n9p282
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Graders and Comparison with an Automated Algorithm for Vertical Cup-Disc Ratio Grading in Fundus Photographs

Abstract: Introduction: We aimed to investigate the intergrader and intragrader reliability of human graders and an automated algorithm for vertical cup-disc ratio (CDR) grading in colour fundus photographs. Materials and Methods: Two-hundred fundus photographs were selected from a database of 3000 photographs of patients screened at a tertiary ophthalmology referral centre. The graders included glaucoma specialists (n = 3), general ophthalmologists (n = 2), optometrists (n = 2), family physicians (n = 2) and a novel au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…These findings were attributed to theoretical teaching that was primarily conducted in the first year of the residents' training. Besides, another study reported no significant correlation between VCDR's graders' reliability and their years of experience in grading [6]. In our study, the clinical optometry trainees were taught about the ways to discriminate VCDR when they were in Year 2.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…These findings were attributed to theoretical teaching that was primarily conducted in the first year of the residents' training. Besides, another study reported no significant correlation between VCDR's graders' reliability and their years of experience in grading [6]. In our study, the clinical optometry trainees were taught about the ways to discriminate VCDR when they were in Year 2.…”
Section: Discussionmentioning
confidence: 48%
“…CDR can be measured horizontally or vertically, giving the horizontal cup-to-disc ratio (HCDR) and vertical cup-to-disc ratio (VCDR), respectively. VCDR is usually used as an indication for glaucoma screening [1,[4][5][6]. An illustration of the ONH and VCDR is shown in Fig 1 . VCDR equal to or larger than 0.8, or a difference in VCDR between eyes by more than 0.2, is pathological [7].…”
Section: Introductionmentioning
confidence: 99%
“…5 It is commonly accepted and has been incorporated into eye health guidelines for optometrists and ophthalmologists. 7 , 8 The DDLS is limited as a diagnostic tool by the need for expert time to accurately grade images. Automated high-efficacy DDLS grading could offer a powerful screening method.…”
mentioning
confidence: 99%
“…First, studies have shown that automated algorithms can offer more consistent and reliable grading than human graders. 8 Second, there has been a rapid advancement in image segmentation, image processing, and deep learning neural networks. In other fields, several neural networks outperformed human graders in image classification tasks.…”
mentioning
confidence: 99%